Figurative Devices in Selected American Military Creeds - Ayad Hameed Mahmoud; Alyaa Husein Abd Fatah (JELITA, 2023)
Military discourse has a considerable impact on the lives of people all over the world, yet only few scholars have paid considerable attention to this sort of discourse. This leads to an obvious need to investigate this genre from different perspectives including stylistics which is the main concern of this study. The study is intended to stylistically analyze a sample of three American military creeds. The study hypothesizes that American military creeds have their own figurative devices which make them distinct texts, and that the figurative devices employed in military creeds vary in terms of their frequencies and functions. The study also hypothesizes that, being written discourse, military creeds are figuratively based, and that the employed figurative devices have a complementary role. They all contribute together to fulfill the creeds’ aims and convey their intended messages. The selected samples are analyzed in the light of Leech and Short’s (2007) model which accounts for figurative devices. The results of analysis show that military creeds have their own distinctive stylistic features, and they are figuratively based. The results also show that the stylistic figurative devices characterizing military creeds have a complementary role in that they all contribute together to achieve the creeds' aims and convey their intended messages.